Modules close to the automorphism-invariant and coinvariant - Truong Cong Quynh; Abyzov, Adel Nailevich; Nguyen Thi Thu Ha; Yildirim, Tulay (World Scientific Publ Co Pte Ltd, 2019)
The aim of this paper is to introduce a general setting where some well-known results on essentially injective modules, automorphism-(co)invariant modules and small projective modules can be obtained by developing a general theory of modules which are (co)invariant under automorphisms of their covers and envelopes.
Keywords: Essentially injective module; small projective module; automorphism-invariant module; automorphism-coinvariant module